Analisis upaya peningkatan minat dan antusiasme anak-anak dalam mengikuti proses pembelajaran: Studi pada TPQ Thalibul Haq - Putra, Gilang Chaya (Maliki Interdisciplinary Journal, 2025)
TPQ Thalibul Haq is an Islamic religious education institution in the city of Malang. TPQ Thalibul Haq was founded with the aim of providing Al-Qur’an education and Islamic teachings to Muslim children in an effort to shape their Islamic character. One of the main objectives of TPQ Thalibul Haq is to help students understand, read, and memorize the Al-Qur’an. Teachers at Thalibul Haq Qur’an Education Park (TPQ) often face various obstacles when teaching. One of these obstacles is how to increase children’s interest and enthusiasm in participating in the learning process. The results of the research state that the efforts made by TPQ teacher Thalibul Haq to increase children’s interest and enthusiasm in participating in and attending the process of teaching and learning activities by implementing several things including creative learning methods, forming study groups, using technology wisely as a means of support, and involving the role of parents. By implementing these learning strategies, TPQ Thalibul Haq was able to create a more engaging and interactive learning environment, thereby increasing children’s interest and enthusiasm for learning the Quran. This effort demonstrates the critical role of innovative teaching methods and collaboration between teachers, students, and parents in enhancing the effectiveness of religious education at the elementary level.